2009
DOI: 10.1016/j.tem.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial protein phosphorylation: instigator or target of lipotoxicity?

Abstract: Lipotoxicity occurs as a consequence of chronic exposure of non-adipose tissue and cells to elevated concentrations of fatty acids, triglycerides and/or cholesterol. The contribution of mitochondria to lipotoxic cell dysfunction, damage and death is associated with elevated production of reactive oxygen species and initiation of apoptosis. Although there is a broad consensus on the involvement of these phenomena with lipotoxicity, the molecular mechanisms that initiate, mediate and trigger mitochondrial dysfun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 111 publications
(173 reference statements)
1
21
0
Order By: Relevance
“…Associated with elevated levels of follicular free fatty acid, obvious lipid accumulation was detected in oocytes from HFD mice [188]. When exposed to a high-lipid environment, cells accumulate triglyceride droplets and free fatty acids, causing significant damages to other cellular organelles, such as mitochondria and endoplasmic reticulum (ER); this process is termed lipotoxicity [206]. Mitochondrial dysfunction and ER stress in oocytes from obese and insulin-resistant mice have been reported by different groups [153, 170, 180, 188, 189, 200].…”
Section: Methodsmentioning
confidence: 99%
“…Associated with elevated levels of follicular free fatty acid, obvious lipid accumulation was detected in oocytes from HFD mice [188]. When exposed to a high-lipid environment, cells accumulate triglyceride droplets and free fatty acids, causing significant damages to other cellular organelles, such as mitochondria and endoplasmic reticulum (ER); this process is termed lipotoxicity [206]. Mitochondrial dysfunction and ER stress in oocytes from obese and insulin-resistant mice have been reported by different groups [153, 170, 180, 188, 189, 200].…”
Section: Methodsmentioning
confidence: 99%
“…One hypothesis for the alteration in mitochondrial function is lipotoxicity, which has mostly been discussed in the context of muscle and liver and which can occur during adipose tissue hypertrophy, usually coupled to adipose tissue insulin resistance, when storage capacity of the adipocyte is exceeded. In this context, it was reported that the mitochondrial phosphoproteome is substantially altered, in response to a lipid overload; however, it remains unclear whether altered mitochondrial function is the driver of lipotoxicity or vice versa [59]. Several interventions have been described, which can reverse the phenotype of reduced mitochondrial function in WAT in obesity, the two most prominent examples being caloric restriction and treatment using PPARÎł agonists [60].…”
Section: Impact Of Age On Mitochondria: Biogenesis Function Bioenermentioning
confidence: 99%
“…Comparative mitochondrial proteomics in different tissues of diabetic animal models have gained insights into the pathogenesis of diabetes and its complications, thus could provide more information for the development of drugs for the treatment of diabetes. Though great progress has been made in mitochondrial proteomics in diabetes, most of these studies solely focused on protein expression, however, mitochondrial protein post-translational modifications, such as phosphorylation, also played crucial roles in mitochondrial functioning (Thomson, 2002;Pagliarini and Dixon, 2006) and mitochondrial perturbations (Graier et al, 2009). Further studies to examine the changes in mitochondrial protein post-translational modifications with proteomic tools in diabetes affected animal model tissues, could provide more information and increase our understanding of the pathogenesis of diabetes.…”
Section: Future Perspectives and Concluding Remarksmentioning
confidence: 99%